2019
DOI: 10.1371/journal.pone.0225181
|View full text |Cite
|
Sign up to set email alerts
|

Early rise in central venous pressure during a spontaneous breathing trial: A promising test to identify patients at high risk of weaning failure?

Abstract: BackgroundThe spontaneous breathing trial (SBT) assesses the risk of weaning failure by evaluating some physiological responses to the massive venous return increase imposed by discontinuing positive pressure ventilation. This trial can be very demanding for some critically ill patients, inducing excessive physical and cardiovascular stress, including muscle fatigue, heart ischemia and eventually cardiac dysfunction. Extubation failure with emergency reintubation is a serious adverse consequence of a failed we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…This resut is consistent with Dubo' finding which an early rised CVP levels after extubation increases the risk of extubation failure. 20 However, this association was not before extubation. Since cardiovascular dysfunction may be difficult to detect in patients with positive pressure ventilation 29 , it is difficult to detect cardiac dysfunction before extubation by CVP.…”
Section: Discussionmentioning
confidence: 92%
“…This resut is consistent with Dubo' finding which an early rised CVP levels after extubation increases the risk of extubation failure. 20 However, this association was not before extubation. Since cardiovascular dysfunction may be difficult to detect in patients with positive pressure ventilation 29 , it is difficult to detect cardiac dysfunction before extubation by CVP.…”
Section: Discussionmentioning
confidence: 92%
“…Noninvasive monitoring of some related indicators may also be used to predict risks introduced by extubation. For example, Dubo et al reported that early CVP (central venous pressure) after SBT initiation may indicate elevated risk of extubation failure [ 20 ]. Keyal et al suggested that patients with invasive mechanical ventilation who successfully completed SBT should be guided by arterial blood gas monitoring to improve extubation success [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Korea described that critical care patients who undergo SBT on low level of pressure support ventilation (ranging from +5 to +10 cmH2O, Positive end expiratory pressure (PEEP) 4 -5 cmH2O) has a successful extubation rate compared to those patients who were not followed the said process (12). Another study found that the patients were eligible for SBT will be ventilated with 5 cmH2O of PEEP and pressure support before starting the SBT and the SBT was performed on "T-piece" that connected to the oxygen source for 1-or 2-hours duration will be decided by their attending physicians (13). After that, those patients were extubated once they were successfully undergone the SBT period (13).…”
Section: The Criteria For Extubationmentioning
confidence: 99%
“…Another study found that the patients were eligible for SBT will be ventilated with 5 cmH2O of PEEP and pressure support before starting the SBT and the SBT was performed on "T-piece" that connected to the oxygen source for 1-or 2-hours duration will be decided by their attending physicians (13). After that, those patients were extubated once they were successfully undergone the SBT period (13).…”
Section: The Criteria For Extubationmentioning
confidence: 99%
See 1 more Smart Citation